2015
DOI: 10.2147/ijwh.s75311
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for postnatal depression assessing the mother–infant relationship and child developmental outcomes: a systematic review

Abstract: Postnatal depression (PND) has negative effects on maternal well-being as well as implications for the mother–infant relationship, subsequent infant development, and family functioning. There is growing evidence demonstrating that PND impacts on a mother’s ability to interact with sensitivity and responsiveness as a caregiver, which may have implications for the infant’s development of self-regulatory skills, making the infant more vulnerable to later psychopathology. Given the possible intergenerational trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 89 publications
1
38
1
1
Order By: Relevance
“…The extent to which CBT and other psychotherapies address parent-child aspects of PND has been questioned (O'Hara and McCabe 2013). In a systematic review of 19 studies, psychological therapies were not found to have a significant impact on mother-infant-relationships despite improvements in PND (Tsivos et al 2015). Mothers in the current study perceived some impact on confidence as a parent as with as relationships with their infants even if this was indirectly via improvements in mood.…”
Section: Therapy Outcomes: Interpersonal Changescontrasting
confidence: 57%
See 1 more Smart Citation
“…The extent to which CBT and other psychotherapies address parent-child aspects of PND has been questioned (O'Hara and McCabe 2013). In a systematic review of 19 studies, psychological therapies were not found to have a significant impact on mother-infant-relationships despite improvements in PND (Tsivos et al 2015). Mothers in the current study perceived some impact on confidence as a parent as with as relationships with their infants even if this was indirectly via improvements in mood.…”
Section: Therapy Outcomes: Interpersonal Changescontrasting
confidence: 57%
“…Both individual and group-based psychological interventions have been shown to be effective in reducing symptoms of depression (Cuijpers et al 2008; Dennis and Hodnett 2007;Scope et al 2013). Historically, psychological therapies for PND have focused on depression symptoms and less on mother-infant outcomes, including the mother-infant-relationship or the infant's development (e.g., see Tsivos et al 2015). Evaluations of parent-child outcomes indicate that traditional psychosocial and psychological therapies for PND do not lead to significant improvements in these areas, even when symptoms of PND have improved (Cooper et al 2003;Cooper et al 2010;Tsivos et al 2015).…”
mentioning
confidence: 99%
“…Education to vulnerable parents how to respond appropriately and optimally to their temperamentally reactive infants is claimed to be central to forming secure attachment (Tsivos, Calam, Sanders, & Wittkowski, 2015). Others studies have also illuminated the importance the instructor have in educating the parents (Oswalt et al, 2009;Underdown et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal depression was assessed by the Center for Epidemiological Studies-Depression (CES-D) scale and anxiety and anger were measured by the Spielberger state anxiety and state anger scales in this study [64,65]. Even though the peer support group had lower socioeconomic status and higher depression scores at the beginning of treatment as well as having shorter group sessions, the groups were equivalent on depression scores at the end of the treatment period.…”
Section: Complementary Interventionsmentioning
confidence: 99%